Motor and Somatosensory Symptoms Determine Cognitive Error Levels in Functional Neurological Symptom Disorder/Conversion Disorder - Orum, Mehmet Hamdi; Atmaca, Murad (Medical University of Plovdiv, 2022)
Introduction: The level of cognitive error in functional neurological symptom disorder (FNSD, conversion disorder) subtypes [psychogenic non-epileptic seizure (PNES), motor (M), PNES plus motor (PM), motor plus somatosensory (MS)] have not yet been investigated. Aim: We aimed to qualify the level of cognitive error in FNSD subtypes. Materials and methods: The disorder symptoms were assessed via the somatoform dissociation questionnaire (SDQ), the symptom check list-90-revised (SCL-90-R), and the global assessment scale (GAS). The cognitive distortions scale (CDS) was used to evaluate cognitive errors. Results: Mean ages of groups were 28.37±6.99 years (PNES, n=24), 27.90±6.22 years (M, n=21), 30.36±7.86 years (PM, n=19), 31.38±9.02 years (MS, n=21), and 30.87±7.17 years (control, n=48) (p=0.377). In terms of the global severity index of SCL-90-R, there were significant differences between PNES and PM (p=0.003); PNES and MS (p<0.001); M and MS (p<0.001); PM and MS (p=0.001). The scores of CDS-IP were similar between PM and M (p>0.999); PM and MS (p=0.172). There was no significant difference between the CDS-PA scores of the patient groups (p>0.05). Conclusions: Our study demonstrated that in FNSD, the somatosensory symptoms were more associated with cognitive errors related to interpersonal relationships than the motor symptoms and the motor symptoms were more than PNES. Copyright by authors.
???????? ? ??????????????? ???????? ?????????? ?????? ??????????? ?????? ??? ?????????????? ??????????????? ?????????? ????????????/????????????? ????????????
Keywords: cognition; conversion disorder; functional neurological symptom disorder; psychogenic non-epileptic seizure